Six sigma for operational excellence - Antony, Jiju; Seow, Christopher (TQM magazine, 2004)
Since its inception more than a decade ago, six sigma as a quality improvement framework has been gaining increasing attention and acceptance in industry. Thus performance in both manufacturing and service operations can now be calibrated in terms of "sigma level", and companies eager to impress customers have begun to label themselves "six sigma organizations". In this paper, a realistic view is taken of the six sigma framework, with an examination of the basis of six sigma and its long term potential. It is argued that in the dynamic business environment of the twenty-first century, a forwar